The Computational Unified Field Theory (CUFT) Goes Beyond the Standard Model: G-d's Physics (Global Journal of Science Frontier Research, 2019)
Physics has reached a "Paradigmatic Crisis" calling for a basic "Paradigmatic-Shift" in 21 st century Theoretical Physics; The new "Computational Unified Field Theory" Paradigm may be called "G-d's Physics" in that it describes the operation of a singular (higher-ordered) "Universal Consciousness Reality" which creates-"dissolves"-re-creates-and evolves every exhaustive spatial pixel in the universe at the incredible rate of "c 2 /h = 1.36 -50 sec' (!) This article delineates the way in which this new 'G-d Physics' goes beyond the "Standard Model" based on the CUFT's new 'A-Causal Computation' Paradigm and its complete unification of the four basic physical features of 'space', 'time', 'energy' and 'mass' as secondary computational derivatives of this singular 'Universal Consciousness Reality's' computation of the degree of "consistency/inconsistency" pertaining to each exhaustive spatial pixel across a series of "Universal Frames". Indeed, this new 'G-d's Physics' Paradigm challenges and negates some of the basic assumptions of 20 th century's" Material-Causal" Paradigm underlying Relativity Theory (RT) and Quantum Mechanics (QM), including: the "Big-Bang" Model, the existence of "dark-matter" and "dark-energy" and even General Relativity's Einstein's Equations! Finally, this new CUFT's "G-d's Physics" goes beyond the 'Standard Model' in that it negates the existence of the four basic "forces" -as "independent" forcesrather seeing them as produced by the singular (higher-ordered) 'Universal Consciousness Reality' (UCR) which exists both "during" its computation of each exhaustive spatial pixel comprising each consecutive UF's frame/s, and solely existing without the presence of any physical universe "in-between" any two such UF's frames! GJSFR-A Classification: FOR Code
Keywords: Paradigmatic Crisis; Universal Consciousness Reality